A case study on failure of AISI 347H stabilized stainless steel pipe in a petrochemical plant. (October 2017) - Ghalambaz, M.; Abdollahi, M.; Eslami, A.; Bahrami, A.
Highlights: A detailed investigation on failure of stabilized stainless pipe was performed in this study. Cracking initiated from the outer side of pipe and propagated in the heat affected zone (HAZ). Thermal fatigue crack growth and formation of chromium rich phase during welding and service condition lead to pipe failure. Abstract: In this study failure of AISI 347 stabilized stainless steel pipe after 60, 000 of working in a petrochemical plant was investigated. Result showed that the main cause of failure was thermal stress fatigue. Fatigue cracks were formed at the outer surface of the investigated pipe, and were grown towards the inner surface at the fusion line of welded area. The formation of chromium-rich phases together with thermal fatigue stresses were found to be main causes of failure.